Managing in Diversity: the Major Domain and Contemporary Transitions (Facets of Managing in Cross-Cultural Diversity, 2021)
Diversity has been a popular term both in theory and practice for many decades, especially with globalization. This chapter discusses diversity and diversity management with special reference to cultural diversity. The aim of this chapter is to understand: how diversity has been viewed and explained, what concepts and models explain diversity, what solutions are given in managing diversity, and what the future of managing cultural diversity might be. A targeted literature review was carried out for the purpose, using journal articles, selected books, theses and documents, as well as other open web sources. The review outcomes show that: diversity has been viewed differently in different times, it is mainly explained in terms of its cognitive and cultural dimensions, diversity management has been mainly targeted for performance improvements, and in the future managing cross-cultural diversity is likely to focus on enabling individuals to be more successful in different cultures, based on their cultural competencies and intelligence, rather than on ethnocentric views towards other cultures.